EDUKASI PEMANFAATAN TANAMAN JAMBU BIJI UNTUK MENINGKATKAN KESEHATAN DIRANGKAIKAN PEMERIKSAAN KESEHATAN MASYARAKAT KELURAHAN TATURA UTARA - Yanuarty, Rezky; Rezky, Fajria; Halik, Nur (Universitas Mataram, 2025)
The biodiversity that grows on this earth is not only used as food or just to enjoy its beauty. Some biodiversity can be used as ingredients in treating several types of diseases. The State of Indonesia is a country that has abundant natural resources. Some of Indonesia's natural resources are used for medicinal materials. One of them is the guava plant which has been widely used for traditional medicine. The guava plant has been widely used in the community both from the leaves to the fruit. Guava leaves contain alkaloid compounds, saponins, tannins, flavonoids, polyphenols, quinones, essential oils. The fruit is high in vitamin C and iron. The purpose of community service is to provide education on its use and how to use it for traditional medicine treatment. Counseling is carried out by lecture method and distributing leaflets. Continuing with material related to the contents and how to treat various diseases, then discussion and question and answer sessions, then continued with free health checks to check blood sugar, cholesterol and uric acid levels. After that, distributing questionnaires is intended so that the extension workers get information related to the PkM that is carried out, whether the community feels happy and gets input from the community for the next PkM activities. The results obtained after conducting counseling, were obtained 86.33% with very good results. It shows that the community is satisfied with the PkM activities and is willing if this activity is carried out again. Conclusion community service activities provide benefits in guava plants and new knowledge related to the benefits and processing them into traditional medicine, which can be practiced to improve public health, especially RT 01 North Tatura Village.